2005
DOI: 10.1128/jcm.43.6.2629-2634.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Antibiogram Analysis Using NCCLS M39-A Guidelines

Abstract: Lack of standardization in antibiogram (ABGM) preparation (the overall profile of antimicrobial susceptibility results of a microbial species to a battery of antimicrobial agents) has not been addressed until recently. The objective of this study was to analyze current antibiograms using the recently published NCCLS M39-A guidelines for preparation of antibiograms to identify areas for improvement in the reporting of antibiogram susceptibility data. Antibiograms from across the United States were obtained by v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 20 publications
0
51
0
1
Order By: Relevance
“…Respondents reported publishing at least annually (98%), eliminating duplicates (89%), not including surveillance cultures (83%), and including at least 30 isolates for each organism (64%) (10). Studies that assessed compliance by direct inspection of antibiograms showed lower adherence than those that used self-reported compliance (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Respondents reported publishing at least annually (98%), eliminating duplicates (89%), not including surveillance cultures (83%), and including at least 30 isolates for each organism (64%) (10). Studies that assessed compliance by direct inspection of antibiograms showed lower adherence than those that used self-reported compliance (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Gram positive and gram-negative isolates bacterial sensitivity to commonly used antimicrobials (amoxicillin, cephalothin, gentamicin) were investigated by disk diffusion method using NCCLS guidelines [20,21] Data were entered and analyzed by Stata v. 8. Person identification code was used as primary sampling unit.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to emphasize that the increasing challenge and complexity of antimicrobial susceptibility testing, analysis and reporting requires the interdisciplinary collaboration and efforts of microbiologists, epidemiologists, clinicians and pharmacists in order to generate and communicate the most accurate and useful susceptibility data possible [1,4,5] . The RDT model developed here is an example of this type of interdisciplinary approach and one that we believe provides a relatively straightforward yet dynamic therapeutic guide and therapeutic decision-making learning tool.…”
Section: Resultsmentioning
confidence: 99%
“…The RDT model discussed here may also serve as a more effective tool to understand the prevalence of different resistant phenotypes in a given institution compared to the traditional ABGM. Lastly, the RDT model developed here represents an interdisciplinary collaboration between microbiologists, pharmacists and infection control practitioners as it relates to the complex problem of antimicrobial resistance, an approach that is currently recommended by the infectious disease and infection control community [4,5] .…”
Section: Introductionmentioning
confidence: 99%